2012
DOI: 10.4081/or.2012.e13
|View full text |Cite|
|
Sign up to set email alerts
|

Repetitive recombinant human bone morphogenetic protein 2 injections improve the callus microarchitecture and mechanical stiffness in a sheep model of distraction osteogenesis

Abstract: Evidence suggests that recombinant human bone morphogenetic protein 2 (rhBMP-2) increases the mechanical integrity of callus tissue during bone healing. This effect may be either explained by an increase of callus formation or a modification of the trabecular microarchitecture. Therefore the purpose of the study was to evaluate the potential benefit of rhBMP-2 on the trabecular microarchitecture and on multidirectional callus stiffness. Further we asked, whether microarchitecture changes correlate with optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Segmental defects are very difficult to manage, as multiple phases of surgery are usually required to achieve an adequate union and to regain the function of bone. Although current treatment options such as autografts, allografts, and distraction osteogenesis have yielded some successes [1][3], serious consequences such as leg shortening or amputation may result if the treatment fails. To overcome these limitations, tissue engineering by delivering therapeutic substances such as bone morphogenetic proteins (BMPs) to the segmental defect to facilitate bone regeneration has been attempted [4][6].…”
Section: Introductionmentioning
confidence: 99%
“…Segmental defects are very difficult to manage, as multiple phases of surgery are usually required to achieve an adequate union and to regain the function of bone. Although current treatment options such as autografts, allografts, and distraction osteogenesis have yielded some successes [1][3], serious consequences such as leg shortening or amputation may result if the treatment fails. To overcome these limitations, tissue engineering by delivering therapeutic substances such as bone morphogenetic proteins (BMPs) to the segmental defect to facilitate bone regeneration has been attempted [4][6].…”
Section: Introductionmentioning
confidence: 99%
“…Differentiation of stem cells into chondrogenic and osteogenic cells might occur in the third week, creating a biological environment that is optimum for new bone formation. [10][11][12] This study used cortical bone graft as material to fill the bone defect because long bone defect fracture needs firm structural support that could not be fulfilled by a cancellous bone graft. The synthetic bone graft is not chosen because of the extra cost needed and the possibility of immunological rejection.…”
Section: Discussionmentioning
confidence: 99%
“…In an ovine model of bone distraction, the osteogenic potential of rhBMP2 at a dose of 4 mg/day on days 3, 10, and 17 after distraction of the tibia was evaluated and it was observed that 3 days of treatment were sufficient to regenerate normal trabecular microarchitecture [34]. However, the production of recombinant proteins is still a costly process and treatment requires repeated applications, which increases the cost of therapy.…”
Section: Discussionmentioning
confidence: 99%